PO063 Utility of mri in central and peripheral neuropathic pain (np). (1st December 2017) - Orellana, Patricia; Campero, Mario; Angus-Leppan, Heather; Guiloff, Roberto
Abstract : Introduction: There is little information on the usefulness of MRI in the management of NP. We prospectively compared its contribution to the management of patients with and without NP. Methods: Patients (n=81):Mean age 56±14. PNS (n=40) (32 polyneuropathies, 8 focal PNS), CNS (n=25) and combined CNS and PNS disease (n=16), each subdivided as painful (NP+) or painless (NP-). NP+ (n=59), NP- (n=22). MRI (n=81) Siemmens Symphony 1.5T, brain and whole spine. MRI classification: Concordant: diagnostic/consistent with the initial clinical diagnosis. Discordant: findings not pathologically significant, unexpectedly normal, or unsuspected significant pathology found related or unrelated to the neurological diagnosis. Fisher´s exact test to compare proportions. Results: Concordant MRIs (n=62): NP +79%, NP- 77% (p=1.0); proportions of NP +and NP- not significantly different within the PNS, CNS and CNS and PNS groups. Discordant MRIs (n=26): NP +30.5% NP-36.3% (p=0.8); proportions also not significantly different within the above groups. 13 (50%) showed significant unsuspected pathology (10 NP+, 3 NP-). MRI changed the initial anatomopathological diagnosis in 11/81 patients (13.5%) (8 NP+, 3 NP-). Conclusions: 22% of patients with neuropathic pain had complex pathology involving both the PNS and CNS. The diagnostic yield of MRI was similar in NP+and NP- patients. Neurological and MRI assessments are essential for patients with neuropathic pain as for patients with similar but painless pathology. *Funding: Fondecyt1120339